Early oral feeding versus traditional feeding after transanal endorectal pull-through procedure in Hirschsprung's disease - Ashjaei, Bahar (Medicine (Baltimore), 2019)
Our study questioned whether the outcome of postoperative early oral feeding is different from traditional postoperative feeding in children with Hirschsprung's disease who underwent transanal endorectal pull-through. This was an observational and comparative study. Patients were allocated into 2 groups. Age, gender, fever, surgery-related infectious, abdominal distension, bowel obstruction, need for reoperation, peritonitis, anastomosis leak, and abscess formation were assessed. IV fluids and antibiotics usage were recorded. A Chi-square test, independent sample unpaired Student t test and Mann–Whitney test were used. P-value < .05 was considered statistically significant. Infections occurred in no patient in group 1 and 1 patient in group 2. Stenosis occurred in 3 patients in group 1 and 2 patients in group 2. Abdominal distension occurred in 4 patients in group 1 and 3 patients in group 2. Fever occurred in 2 patients in group 1 and 1 patient in group 2 within the first 24 hours and it occurred in 13 and 17 patients, respectively, within 48 hours. All patients of group 1 (n = 15) were treated with antibiotics and intravenous fluid administration; 1 patient for 24 hours, 12 patients for 48 hours, and 1 for 72 hours, respectively. All patients of group 2 (n = 18) were treated with antibiotics and intravenous fluid administration for 5 days. We noted a significant difference regarding the duration of antibiotic treatment and intravenous fluid administration after 72 hours. This study showed that there was no difference between the outcomes of early and traditional postoperative feeding. Due to a significant difference in the antibiotics and IV fluid administration intervals between these 2 groups which cause a prolonged hospital stay and higher costs, it seems that early postoperative feeding is superior to traditional strategy.